Study on the stability of waste rock filling in goaf based on dynamic comprehensive analysis method - Gongyong Wu; Xingxin Nie; Linhai Zhao; Zongli Li (Heliyon)
The restoration and treatment of underground voids have always posed significant challenges for constructing environmentally sustainable mines. To investigate the effectiveness of a combined approach involving waste rock filling and grouting roof filling as treatment methods to ensure safety and stability in mining voids, this study employed a comprehensive dynamic analysis approach. It specifically focused on an individual underground metal mine cavity by integrating numerical simulation analysis techniques with onsite displacement monitoring methods. By simulating stress-strain conditions during different stages of cavity formation and subsequent treatments while considering onsite displacement monitoring data, this study extensively analyzed how these treatments impact rock stress levels, strain conditions within rocks themselves, and the stability of the surface riverbed. The results show that: (1) ''waste rock filling + cemented roof filling'' can effectively reduce the stress of surrounding rock, significantly improve the structural stability of goaf, reduce surface displacement and deformation, and ensure the stability of surface riverbed; (2) In the process of mining and filling, the stress and strain sensitive points are mainly distributed in the roof, bottom and intercolumn of the stope; (3) When the goaf is backfilled from top to bottom, the stress-strain changes at each stage are uneven: the maximum principal stress changes slowly in the early stage, but greatly in the later stage; The change of displacement showed a trend of slowing down in the early stage and stabilizing in the later stage: (4) ''waste rock filling + cemented filling'' roof joint can realize the transformation of solid waste into treasure in mines, effectively promote the construction of green mines, and is an effective means of goaf treatment. It provides ideas and means for other similar complex problem analysis and prevention.